Structured discharge plan and self-care abilities among adult patients with heart failure - Yumul, Marjorie B. (2003)
The study was conducted to determine the effects of a structured discharge plan (SDP) on the self-care abilities (SCA) of adult patients with heart failure. Specifically, this sought to determine: 1) if there is a difference in the self-care abilities of patients who were given structured discharge plan from those who did not, 2) which among the extraneous variables correlate significantly with self-care abilities. The non-equivalent post-test-control group design was used in the study. The structured discharge plan (SDP) was provided to patients with heart failure from two government tertiary hospitals: Philippine General Hospital and Ospital ng Maynila Medical Center. The post-discharge measure for self-care abilities (SCA) were done in the home setting one to two weeks after discharge from the hospital. The tools utilized to obtain data were: (1) the client's personal data form to elicit socio-demographic data (2) Questionnaire on perception of compliance to diet, medications, and fluids (3) Self-Care Ability Checklist. There were forty-five (45) adult patients (control = 22; study = 23) in the study. Fifty six percent (56%) were males and forty-four percent (44%) females. The mean age is 49 years. Majority of the subjects were married and had eight (8) mean years of schooling. Both groups had high mean score in their perception of compliance to diet. Fifty-one percent (51%) had one to two hospital confinements for the same medical diagnosis. The average length of hospitalization was ten days. Ninety-six percent (96%) had co-morbidities. The mean number or medication actually take was five with estimated cost of Php76.10 per day. Five sources of social support were identified: spouse, other relatives, children, siblings and friends. Of the three type of social support, financial was identified as most important. The self-care were measured using six categories were: bathing (0.67), dressing (0.47), mobility and walking (0.35), toileting (0.34), feeding (0.30) and grooming (0.25). Slight difference in the over all mean score of self-care abilities was noted between the two groups: control = 19.04 (SD = 5) while the study group obtained a mean score of 21.41 (SD = 3.61). However, the t-test did not show any statistical significance (p = .079). The study group generally perceived the usefulness of the SPD to enhance their self-care capabilities. Strategies for energy conservation were utilized and cognitive level reflected better understanding of the health condition. Extraneous variables such as age, number of hospital confinements, number of prescribed medications actually taken by clients, presence of co-morbidity and perception of compliance did not significantly correlate with self-care abilities using Pearson Product Moment Correlation.
Vita.
Thesis (MA Nursing) -- University of the Philippines, Manila.
Keywords: Self-care, Health; Hospitals -- Admission and discharge